Two-dimensional stability problem for horizontal holes that are in uncompressedelastic - plastic materials with inhomogeneous initial deformation - E. Hazar (MANAS: Journal of Engineering)
Stability problems for cases with unhomogenous initial tensions have been studied and solved in the fromework of Three dimensionel stability theory using variationel metod. Results of the elastikplastik problems for homegenous plastik deformations are in reasonable agremeent with each other